Analisis Pandangan Tuan Guru Terhadap Putusan Talak Satu Pengadilan Agama Praya Atas Kasus Talak Tiga Di Luar Pengadilan Perspektif Pluralisme Hukum : (Studi Di Kecamatan Praya Barat, Lombok Tengah) - Sariatin Hasanah; Sainun; Lalu Muhammad Nurul Wathani (Muhammadiyah University of Surabaya, 2025)
This study aims to reveal the practice of triple divorce outside the Religious Court that occurs in the community of Praya Barat Subdistrict, as well as to map the views of Tuan Guru on the Religious Court of Praya's decision on a case of triple divorce outside the Court. The focus of the study is to analyze the views of Tuan Guru and the basis of the Religious Court of Praya's decision in the context of legal pluralism that developing in society. This study employs a qualitative descriptive approach using the case study method. Data was collected through interviews, observations, and documentation. Analysis utilizes sociological and legal approaches to understand the practice of triple divorce outside the court and Tuan Guru's views on the Praya Religious Court's decision. The results of the study indicate that the practice of triple divorce outside the court still occurs in Praya Barat Subdistrict and is considered valid by the community. The main factors underlying this practice are: religious factors, low legal literacy among the community, cultural, economic, and educational factors. The Praya Religious Court's decision No. 191/Pdt.G/2023/PA.Pra, which originated from divorce outside the court was ruled as a minor divorce by the panel of judges because there was no evidence in the lawsuit stating the existence of triple divorce and no record of previous divorce. Therefore, the panel of judges decided the case based on the facts and evidence presented in court. The response of the Teachers to the ruling varied, but the majority of Teachers in the continued to adhere to the classical fiqh understanding that a triple divorce uttered by the husband remains valid if it meets the requirements of Islamic law. The religious leader argued that divorce registration is an administrative process that serves a public interest but cannot invalidate a divorce that has already been uttered. This response reflects the tension between Islamic law and state law within a pluralistic societal system.